Записки успешного манагера: [роман] / Эмилия Прыткина - Прыткина Э. (АСТ: АСТ Москва: Полиграфиздат, 2010)
Экземпляры: ЦБ (20101129) / Инвентарный номер: 42821 / Цена: 168.85 / Авт.знак: П 85 / ББК: 84(2Рос=Рус)6